CD155, an onco‐immunologic molecule in human tumors. Issue 10 (18th August 2017) - Gao, Jian; Zheng, Qianqian; Xin, Na; Wang, Wei; Zhao, Chenghai
Abstract : CD155 is the fifth member in the nectin‐like molecule family, and functions as the receptor of poliovirus; therefore, CD155 is also referred to as necl‐5, or PVR. As an immunoglobulin‐like adhesion molecule, CD155 is involved in cell motility, and natural killer and T cell‐mediated immunity. CD155 is barely or weakly expressed in various normal human tissues, but frequently overexpressed in human malignant tumors. CD155 overexpression promotes tumor cell invasion and migration, and is associated with tumor progression and poor prognosis. As the ligand for both costimulatory receptor CD226 and coinhibitory receptor TIGIT and CD96 on natural killer and T cells, CD155 seems to play a dual role in oncoimmunity. However, some recent studies indicate that CD155 overexpression may induce tumor immune escape. Taken together, CD155 may be considered as a target for the treatment of tumors with CD155 overexpression. Abstract : CD155 overexpression promotes tumor cell invasion and migration, and is associated with tumor progression and poor prognosis. As the ligand for both costimulatory receptor CD226 and coinhibitory receptor TIGIT and CD96 on NK and T cells, CD155 seems to play a dual role in oncoimmunity. Some recent studies indicate that CD155 overexpression may induce tumor immune escape.